Set Model by Organizational Choice: Human Relations, Knowledge Management and Human Element at the Intersection of Organizational Learning - Sağsan, Mustafa (Information World, 2002)
This study attempts to combine the concepts of human relations, knowledge management and organizational learning. Also, it emphasizes the importance of information management in human relations approach and the process of organizational learning in human relations. A “set model” of these concepts was developed. Consequent results of this model indicaed the necessify for investment in human capital.